Políticas públicas de informação no contexto da abertura do Estado: Perspectivas sobre a atuação da Universidade Federal do Ceará com a Lei de Acesso à Informação. - Furtado, Estenio Façanha (2017)
The work discusses the accessibility by public information triggered recently by law 12,527/12, seeking to identify the implications generated by this access law by the transparency of governmental entities in order to figure out how to change the implementation of public access to information policies. Aimed to investigate the General Applications of the law of access to information in the context of the Brazilian Pro's Office at the Federal University of Ceará, in the light of the information regime. The motivation arose from the desire to answer the following question: how is it possible to understand the application of the access to information law from the Federal University of Ceará through the scheme of information? Among the specific objectives, undertook a discussion of conceptual aspects of information, in order to grasp the complexity that this terminology comes taking in the information society, as well as historical perspectives and conceptual approach of the process of opening of the State and historical foundations and conteudísticos for the emergence of the law of access to information. The intertwining of terms associated with the semantic field of access to information is brought to the surface from the triad advertising x accountability x transparency and your reflexes for a scenario of public governance. We used the information Regime as methodological approach for evaluating the implementation of the provision and access to information as is required by the law of access to information. The perception of the components of that scheme took place based on the achievement of data collection through interviews and questionnaires semi-enclosed seas in three pró-reitorias of UFC: PROGEP, PROPLAD and PROGRAD, in order to investigate the actors, devices, artifacts and information actions in the practices of the Federal University of Ceará relating to meeting the demands of active and passive transparency required by Law. It was found that the LAI is obeyed by the UFC, with support in the analysis of information of the system, but your compliance is not enough to observe the occurrence of a collaborative transparency. It was noted that arrangements for the provision of public information is in the process of implementation by the Federal Government as part of a process of reform of the State gerencialista, whose core aims to bring the public entities of the citizens as the effectiveness of the transparency to occur with greater property. It was verified the existence of a multifaceted scenario of implementation of various activities designed to promote citizen information so that the law 12.527/11 consolidates itself as the legal element of greater relevance in the implementation of ongoing Information Regime